1984
DOI: 10.1136/oem.41.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to cotton dust in an experimental cardroom.

Abstract: ABSTRACr Changes in respiratory function (FEV,) and polymorphonuclear neutrophils (PMN) on nasal epithelium were studied in 68 students and 39 cotton mill workers in an experimental cardroom. The exposure was characterised by the vertical elutriator dust and endotoxin levels. A dose related decrease was found for FEV, which was more pronounced in smoking workers. The thresholds for no FEV, reaction were 0-58 mg/i3 dust and 0*17 ,g/m3 endotoxin for students and 0-43 mg/m3 and 0.08 ug/m3 for smoking workers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 9 publications
3
39
0
1
Order By: Relevance
“…At high dose levels, symptoms can be made to appear also among persons previously without such symptoms and indeed also in subjects previously never exposed to cotton dust (2). The more pronounced decreases in FEV1 among smokers as compared to nonsmokers agrees with earlier studies (8).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…At high dose levels, symptoms can be made to appear also among persons previously without such symptoms and indeed also in subjects previously never exposed to cotton dust (2). The more pronounced decreases in FEV1 among smokers as compared to nonsmokers agrees with earlier studies (8).…”
Section: Discussionsupporting
confidence: 86%
“…Previously, it has been shown that the number of neutrophils on the nasal respiratory epithelium increases over the shift (2). Neutrophils are activated by endotoxin or gram-negative bacteria on cotton dust and could release mediators for inflammation and bronchoconstriction, such as leukotrienes or platelet activating factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haglind and Rylander [95] found in cotton workers and student volunteers exposed to the inhalation of cotton dust in an experimental cardroom, a significant correlation between the concentration of airborne endotoxin and the FEV 1 decrement during the working shift. This relationship was more pronounced in workers who smoked, which suggests that smoking predisposes to enhanced response to inhaled endotoxin.…”
Section: Dust-borne Endotoxins and Allergens Of Pantoea Agglomerans -mentioning
confidence: 94%
“…It is generally believed that acute airway obstruction induced by a short-term exposure to cotton dust is reversible [14][15][16]. However, it is not clear whether chronic airway changes associated with long-term exposure are reversible after the exposure ceases.…”
Section: Discussionmentioning
confidence: 99%